Diversifikasi Produk Tempe Menjadi Nugget sebagai Upaya Peningkatan Gizi Anak dan Pencegahan Stunting - Shafwan Aulia Rahman; Fatimah Aminati; Muhammad Yassir namirudin; Eka Prasetya Budi Mulyawan; Sendi Ibnu Hilmiawan; Ananda Rizky Fadillah; Meilana Afif Mahmudi; Arya Sheva Satria Dewantara; Ayu Safitri; Rosyita Nur Syafa'ah; Al fathih Niska Adilah; Viena Eka Yuadianti; Andriyani Puji Lestari; Arista Anindya Ramadhani; Muhammad Alif Rizky H (Lembaga Pengembangan Kinerja Dosen, 2025)
The Student Organization Capacity Building Program (PPKO) of the PTI FKIP UMS is a community service initiative that aims to increase the added value of tempeh products in Sentono Village, Karangdowo District, Klaten Regency, with a focus on product innovation, particularly tempeh nuggets. Sentono Village has long been known as one of the largest tempeh production centers in Klaten, with more than 26 active tempeh producers. However, these producers face significant challenges in the form of conventional marketing and a lack of diversification in tempeh products, which has resulted in the village's economic potential not being fully realized. This activity was designed to address these issues by actively involving the community, including intensive training in tempe nugget production, hands-on practice under the guidance of facilitators, and interactive question and answer sessions to solve practical problems. To measure the effectiveness of the program, an evaluation was conducted using pre-tests and post-tests to quantitatively measure the increase in participants' knowledge and skills. The results of this evaluation show a significant increase in participants' knowledge and skills, proving that product innovation can be a strategic solution to improve the competitiveness of MSMEs in the modern era.